Effect of Thermomechanical Densification Treatment on Abrasion Resistance of Five US Hardwoods - Snow, Dusty; Khademibami, Laya; Sherrington, Alan; Shmulsky, Rubin; Montague, Iris; Ross, Robert J.; Wang, Xiping (Forest products journal, 2022)
The effect of thermomechanical densification treatment on the abrasion resistance of five hardwood species were investigated in this study. The species tested include ash ( Fraxinus sp.), hickory ( Carya sp.), red oak ( Quercus sp.), sweetgum ( Liquidambar styraciflua ), and white oak ( Quercus sp.). The abrasion test was performed according to the American Society of Testing and Materials standards. Ten specimens from each species were initially tested for abrasion resistance, and those specimens were then put through a thermomechanical densification process. The densification process consisted of bringing the heated platen up to a temperature of 176°C (350°F) on one surface and pressing the specimens at 6.9 MPa (1,000 Psi) for a period of 5 minutes. The densified specimens were then subject to the same abrasion testing procedure. All data were statistically analyzed by two-way analysis of variance (ANOVA) with the procedure of general linear mixed models. The results of this study indicated that densified hickory had the highest abrasion resistance among the five hardwood species tested.